Modeling Inclusive Learning Participation: An Evaluative Study on Teacher Interpersonal Capacity and School Climate Dynamics - Fefri Eka Mariza; Marzuki Noor; Sujino Sujino (Assyfa Learning Journal, 2026)
Despite progressive inclusive education policies in Indonesia, the actual learning engagement of students with disabilities (SWD) remains a critical instructional challenge due to the gap between physical attendance and meaningful classroom participation. This study aims to analyze the quantitative influence of teachers’ social competence and an inclusive school climate on the learning participation of SWD in elementary schools across Metro City. Utilizing a quantitative ex post facto design, data were collected via validated four-point Likert scale questionnaires from a purposive sample of 30 SWD. Multiple linear regression analysis revealed that teachers’ social competence significantly and positively influences learning participation ( = 0.469; ), and an inclusive school climate likewise yields a significant positive effect ( = 0.435;  = 0.004). Simultaneously, both variables synergistically explain 63.2% of the variance in students' learning participation (R2 = 0.632; F = 23.165;  = 0.000). These findings conclude that optimizing instructional environments for SWD requires a holistic socio-organizational framework that integrates teachers' interpersonal empathy with supportive, safe, and diverse institutional structures. Practically, this study implies an urgent need for empathy-based professional teacher development and responsive school policies that shift the evaluation paradigm from mere physical presence to high-quality pedagogical engagement